Dealing with Systemic Sovereign Debt Crises : Fiscal Consolidation, Bail-ins or Official Transfers? - Sandri, Damiano (IMF Working Papers; Working Paper ;, 2015)
The paper presents a tractable model to understand how international financial institutions (IFIs) should deal with the sovereign debt crisis of a systemic country, in which case private creditors' bail-ins entail international spillovers. Besides lending to the country up to its borrowing capacity, IFIs face the difficult issue of how to address the remaining financing needs with a combination of fiscal consolidation, bail-ins and possibly official transfers. To maximize social welfare, IFIs should differentiate the policy mix depending on the strength of spillovers. In particular, stronger spillovers call for smaller bail-ins and greater fiscal consolidation. Furthermore, to avoid requiring excessive fiscal consolidation, IFIs should provide highly systemic countries with official transfers. To limit the moral hazard consequences of transfers, it is important that IFIs operate under a predetermined crisis-resolution framework that ensures commitment.